2017
DOI: 10.1145/3053430
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Field Data for Testing Systems Subject to Incremental Requirements Changes

Abstract: When testing data processing systems, software engineers often use real world data to perform system level testing. However, in the presence of new data requirements software engineers may no longer benefit from having real world data with which to perform testing. Typically, new test inputs complying with the new requirements have to be manually written.We propose an automated model-based approach that combines data modelling and constraint solving to modify existing field data to generate test inputs for tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Our case study material is borrowed from previous work. Specifically, Case A was built for system testing of an eGovernment application concerned with calculating personal income taxes [77], Case B for system testing of an occupant detection system in cars [82], and Case C for system testing of a satellite communication system [28]. Our case study material (in a sanitized form) is available from PLEDGE's website.…”
Section: Description Of Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our case study material is borrowed from previous work. Specifically, Case A was built for system testing of an eGovernment application concerned with calculating personal income taxes [77], Case B for system testing of an occupant detection system in cars [82], and Case C for system testing of a satellite communication system [28]. Our case study material (in a sanitized form) is available from PLEDGE's website.…”
Section: Description Of Case Studiesmentioning
confidence: 99%
“…expand is called recursively over original's children */ originalshortcuts alongside their equivalent expressions with explicit quantification. In the final segment of the algorithm (L [28][29][30][31],. expansion is applied recursively to the children of a visited node.…”
mentioning
confidence: 99%
“…The authors compare the effectiveness of defects found and efficiency in terms of effort spent to complete each process. P8 [9]: In this paper, the authors propose an automated modelbased approach to generate test inputs for testing new data requirements by modifying the old data. P9: [30]: In this paper, the authors design and conduct an empirical experiment to compare manual ad hoc testing with model-based testing with the aid of the TaRGeT tool.…”
Section: Description Of the Primary Studiesmentioning
confidence: 99%
“…For example, the specification has to be extended to deal with new situations. Di Nardo et al 51 presented an automated model-based approach that combines data modelling and constraint solving to modify existing field data to generate test inputs for testing new data requirements. A toolset for automatic conformance testing is presented in Faria and Paiva 52 that enable incremental conformance checking.…”
Section: Conformance Testingmentioning
confidence: 99%